Pengaruh Video Berbasis Anotasi Dalam Flipped Learning Terhadap Beban Kognitif dan Hasil Belajar Siswa SMP - Indri Rahmawati Putri Widodo; Rizki Hikmawan (LPPM Institut Pendidikan Nusantara Global, 2026)
The flipped learning model places initial learning in the pre-class phase through video media; however, its effectiveness is highly dependent on the quality of the video design used because, in practice, students often struggle to understand the material and tend to forget information during in-class learning activities due to poorly managed cognitive load, particularly extraneous cognitive load arising from poorly structured presentations. This study aims to analyze differences in learning outcomes and cognitive load between conventional videos and annotation-based videos in flipped learning. The study employed a one-group repeated-measures posttest-only design, involving 30 eighth-grade students at a junior high school in Purwakarta. Cognitive load was measured using the Cognitive Load Questionnaire, which covers intrinsic, extraneous, and germane cognitive load, while learning outcomes were assessed through a final evaluation test. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon signed-rank test. The results showed that the use of annotated videos reduced intrinsic cognitive load from 3.17 to 1.60 and extraneous cognitive load from 3.16 to 1.49, while increasing germane cognitive load from 2.46 to 3.67. In addition, learning outcomes increased from an average of 66.00 to 92.33 with a significant difference (Z = -4.811) and an effect size of 0.88. These findings indicate that annotated videos can direct students’ attention to essential information, thereby reducing irrelevant cognitive load and enhancing meaningful cognitive processing, which makes learning more effective in a flipped learning environment.